NILAI PATRIOTISME DALAM NOVEL KELUARGA GERILJA DAN IMPLEMENTASINYA SEBAGAI PEMBELAJARAN DI SEKOLAH - Amanda Kalalo, Artha Jeane Claudya Amanda Kalalo, Ahadi; Sulissusiawan, Ahadi; Priyadi, A Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the desire to apply the value of patriotism to students through the novel Gerilja Keluarga by Pramoedya Ananta Toer. The common problem in this research is "What is the value of patriotism in the novel Gerilja Keluarga by Pramoedya Ananta Toer and its implementation as learning in school?". This general problem is limited to 4 subproblems. The purpose of this study is to describe 4 of these sub-problems, while this research is useful for researchers to add knowledge and insight in analyzing literary works, can be used by teachers and students as learning media and as a comparison material for other research.The theory used in this study relates to the value of patriotism, figures, and characterizations. This research uses descriptive methods, qualitative research forms, and uses a sociological approach to literature. The source of research data is the novel Gerilja Keluarga by Pramoedya Ananta Toer. Data collection techniques in this study are documentation, interview, and note taking techniques. The data in this study are patriotism values which are reflected in words, expressions and quotes contained in the Gerilja Family novel.Based on research conducted, researchers managed to collect and analyze 67 quotes that illustrate the value of patriotism contained in the Gerilja Family novel.Keywords: patriotism value, characterization, novel.